A first reported case of clear cell carcinoma associated with delayed extrusion of midurethral tape. Issue 3 (March 2016) - Lin, Harvard; Wu, Fiona; Low, Jeffrey; Venkateswaran, Kotamma; Ng, Roy
Abstract We present the first reported case of clear cell carcinoma associated with a midurethral tape (MUT), the possible hypotheses and the management pitfalls we encountered. We report a 58-year-old woman who presented with symptoms of urinary tract infection and acute retention of urine associated with vaginal tape exposure 10 years after placement of an inside–out transobturator tape. She subsequently had a partial transobturator tape excision and a diagnostic cystoscopy, which revealed inflammatory changes within the urethra. Postoperatively, her symptoms persisted and the vaginal epithelium healed poorly. A biopsy of the friable tissue reported clear cell carcinoma. Imaging showed a locally invasive periurethral mass and bony and lymphatic metastases. This was treated with palliative radiation therapy. She was still receiving palliative care 5 months after the initial surgery.